2014
DOI: 10.1097/der.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reactions to Sunscreen Agents

Abstract: Sunscreen is a key component in the preventive measures recommended by dermatologists and public health campaigns aimed at reducing sunburn, early skin aging, and skin cancer. To maximize compliance, adverse reactions to sunscreens should be minimized. Although inactive ingredients cause many of these reactions, it is important for dermatologists to be aware of reactions to active ultraviolet filters. There are approximately 120 chemicals that can function as ultraviolet (UV) filters. This review focuses on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(16 citation statements)
references
References 145 publications
0
16
0
Order By: Relevance
“…Patients with photodermatitis are likely to develop photo contact dermatitis to sunscreen. 83 Sunscreens containing p-amino benzoic acid (PABA) help to protect from UVB rays and is said to be water resistant. 42 But in vitro studies have shown that PABA interacts with DNA followed by UV radiations and might cause photocarcinogenesis.…”
Section: Toxicity Aspectsmentioning
confidence: 99%
“…Patients with photodermatitis are likely to develop photo contact dermatitis to sunscreen. 83 Sunscreens containing p-amino benzoic acid (PABA) help to protect from UVB rays and is said to be water resistant. 42 But in vitro studies have shown that PABA interacts with DNA followed by UV radiations and might cause photocarcinogenesis.…”
Section: Toxicity Aspectsmentioning
confidence: 99%
“…As the molecule returns to the ground state, it releases the lower energy of longer wavelengths. [ 57 ] Such compounds as Avobenzone, Oxybenzone, Ecamsule, Octinoxate are FDA-approved components of topical sunscreens with different spectrums of absorption and various photostability. Octinoxate is identified as one of the potent UVB-absorbers [ 58 ], but is not photostable and degrades in the presence of sunlight after a short period of time, while Ecamsule, a very photostable product, acts as UVA-blocker.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of physical sunscreens, such as Zinc oxide, Titanium dioxide is based on the reflection and scattering of UV light. The reflective properties - reflective index, the size of the particles, the film thickness, and the dispersion of base determine the effectiveness of inorganic sunscreens [ 57 ]. Microfine zinc oxide has shown to be efficient against a wide range of UVA including UVA 1 (340 to 400 nm), but less efficient in blocking UVB, compared to Titanium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Sunscreens/ultraviolet filters (UV-filters) are mainly used in personal care products, such as lipsticks, perfumes, hairsprays, hair dye and moisturizers, skin care products, shampoos, and makeup, as well as in noncosmetic products, including furniture, plastics, carpets, and washing powder [ 104 , 105 ]. Sunscreens are popular protective products against ultraviolet radiation hazards, early skin aging, and skin cancer [ 106 ]. UV-filter formulations can be organic (chemicals) or inorganic (minerals) [ 107 ].…”
Section: Sunscreens/ultraviolet Filtersmentioning
confidence: 99%
“…Frederiksen et al investigated BP-3, a UV-filter, and found that it could be detected in 96% of American urine specimens and 85% of Swiss breast milk specimens analyzed [ 104 ]; however, UV-filter potential hazards on humans are difficult to assess using exposure data alone. At present, most case reports are related to dermatitis caused by sunscreens [ 106 ]. The associations between sunscreens and adverse effects on humans have not been deeply and widely investigated.…”
Section: Sunscreens/ultraviolet Filtersmentioning
confidence: 99%